EFFECT OF YOGASANA AND AEROBIC EXERCISE ON FLEXIBILITY AND BREATH HOLDING CAPACITY OF HIGH SCHOOL OBESE GIRLS IN KERALA - REMESH. R AND M. SAROJA
Childhood obesity is the result of a long lasting imbalance between energy intake and energy expenditure. A major contributing factor is physical inactivity which is closely linked to bone health, cardiovascular disease risk, fitness and psychological factors. This study was undertaken to examine the effect of yogasana and aerobic exercise on flexibility and breath holding capacity of high school obese girl students in the Kerala State. The sample of the study has been selected randomly. The sample consists of 45 obese students studying in different schools in Kerala State. They were divided in to three groups, namely yogasana group (group A), aerobic group (group B) and control group (group C). The group A&B were participated in the training programme for a period of 6 weeks. The collected data were statistically analysed by using analysis of covariance (ANCOVA)